Documente istorice vechi româneşti – din secolele XIV–XIX – în fondurile Bibliotecii Naţionale a României - Elena Cojuhari (Revista de Istorie și Teorie Literară)
The National Library of Romania, as one of the most important national heritage forums of the Romanian culture and civilization in our country and abroad, holds within its Special Collections a considerable number of old historical documents, issued or referring to the XIV–XIX centuries. The significance of these documents is undeniable. They offer valuable information of political, linguistic, cultural, social, economic and financial interest, data with reference to certain persons, from anonymous to well known figures, information regarding the criminal and civil law practice at the moment of their isssuance. The interpretation/ decipherment of archival materials allows enhancing the present knowledge with different shades, colors, data, papers, deeds specific to the Romanian Orthodox Christian civilization developed in Moldova and Wallachia, beginning from the Middle Ages, in particular, till the second half of the XIXth century, covering distinct periods of time: that of the native rulers, the Phanariots epoch, the Organic Statute period and the dawn of the new era founded along with the two Romanian Principalities Union in the year 1859. Hereupon, the whole picture, obtained as a result of a summary and minimal research of the information given by the documents, becomes much more animated and complex.